Modelo constructivista para el desarrollo del método de proyectos educativos, en el área ciencias naturales, con estudiantes del sexto y séptimo año de educación básica, de la Escuela Atacames, parroquia Taracoa, cantón Francisco de Orellana, provincia Orellana en el período lectivo 2012 - 2013 - Ochoa Cueva, Sonia Esperanza (2013)
Importantly, teachers have a responsibility to provide students with a science background that allows them to take as citizens aware, open-minded for that reason there has been numerous failures to make on the subject based on the constructivist model method development Education Projects Science area with students of sixth and seventh year of Basic Education, School Atacames Taracoa Parish, Canton Francisco de Province for school year 2012 - 2013 ", for there is born problem is defined in the same issue: Ignorance constructivist model, the method prevents the development of educational projects in the area of life science with students of 6th and 7th year of Basic Education Atacames School, Parish Taracoa, Francisco de Orellana Canton , Orellana Province for school year 2012 - 2013? The overall objective. Structuring knowledge constructivist model for method development of educational projects with the linking of theory and practice, the natural sciences to students from 6th and 7th year of basic education. The specific objectives are: Identify the knowledge and skills they have in theory and practice to students with constructivist model application from surveys of students and teachers. Basing the method of educational projects as construction of knowledge, theories with solvency using the technological, ecological, socio - cultural and educational. Offer workshops with educational projects for the demonstration of knowledge and capabilities constructivist in the student task. Our hypothesis: With the constructivist model structuring, execution contributes Method Educational Projects for linking theory and practice in the area of life science with students in sixth and seventh year of basic education Atacames School, Parish Taracoa, Canton Francisco de Orellana Province Orellana. The variables providing job development are independent variable and the dependent variable constructivist method of educational projects. The methodology is oriented according to the teaching work from basic research and descriptive literature field, the selected design is cross between the data collection instrument was taken encaustic teachers and students, interview people and Headmaster sample is taken in a total of forty subjects: A principal, nine teachers 18 students from 6 years and 22 students of seven years a total of 40 research subjects. In the analysis and interpretation of results are presented charts and statistical tables showing the problem that has arisen in the said school. It concluded its work by the need to structure the pedagogical models, particularly constructivism, which has been unknown, so the training of students with empirical transmission, not construct knowledge. Teachers do not work interactively and unknown as learning facilitator, linking theory with practice by consequent are memoirists, mechanistic and theoretical, flat affect, cooperation in the construction of educational projects. The space is intended to build curricular knowledge, generating attitudes towards the environment, considering nature as a privilege in the area of natural science, this source suggests organizing a variety of workshops to discover and learn educational projects for demonstration of knowledge constructivist and student skills in the work. Teachers as learning mediators are able to organize workshops with educational projects for the construction of student knowledge. Develop a process approach for the implementation of knowledge with small projects. Demonstrate through open house educational building projects. Below is a consistent type of educational projects to the sixth and seventh year of basic as it is. Inner and outer layers of the earth, make a volcano erosion, soil texture and structure, hydroponics representation, representation of the food pyramid, adopt a plant, earthworm, transpiration of plants, the anemometer, grassland plant collection, water not let it fall, digestion in humans. The research evidence is presented through the operating plan, detailing the activities and methodology used in the workshop and demonstration of practical work and / or projects built by students and teacher learning mediator, its implementation using the scientific method, quali - quantitative. to conclude the outcome of the proposal was satisfactory knowledge there constructivist model, for consistency, linking theory with practice, ruling memorization, also mentioned that students are able to observe, analyze, compare and reflect critically and argue facts that occur in nature, students have developed productive projects through research, taking the same taste for learning by doing and also teachers are trained to teach and disseminate this learning significant constructivist classroom